W. G. Collingwood artist, art historian, critic, archaeologist, and Anglo-Saxonist - Hawkes, Jane (2015)
This article examines the scholarship of the scholar and artist W. G. Collingwood, perhaps best remembered for his monograph on Anglo-Saxon sculpture (1927). It traces his evolution from the time his Philosophy of Art was published (in 1883), when he entered the inner circle of Ruskin's collaborators and began exhibiting at the Royal Academy, while at the same time embarking on a career as an archaeologist. This essay shows that the attitudes and views revealed in his art and articulated in his art-historical and critical works over the next twenty years remained largely unchanged until the early years of the twentieth century (1907) when he began depicting, commenting, and publishing on early medieval sculpture in largely diagrammatic and formalist terms. While this scholarship marked an apparently significant departure from his work up to that point, and from the approaches that were emerging at the time among other Anglo-Saxon art-historical scholars, it nevertheless reflects a continuity in his work as an archaeologist.
Keywords: Collingwood, William G. -- 1854-1932; Ästhetik; Malerei; Kunstkritik; Archäologie